5-Hydroxymethylation-associated epigenetic modifiers of Alzheimer's disease modulate Tau-induced neurotoxicity. - Bernstein, A.I.; Lin, Y.; Street, R.C.; Lin, L.; Dai, Q.; Yu, L.; Bao, H.; Gearing, M.; Lah, J.J.; Nelson, P.T.; He, C.; Levey, A.I.; et al. (Human Molecular Genetics, 2016)
Alzheimer's disease (AD) is a chronic neurodegenerative disorder characterized by progressive deterioration of cognitive function. Pathogenesis of AD is incompletely understood; evidence suggests a role for epigenetic regulation, in particular the cytosine modifications 5-methylcytosine and 5-hydroxymethylcytosine (5hmC). 5hmC is enriched in the nervous system and displays neurodevelopment and age-related changes. To determine the role of 5hmC in AD, we performed genome-wide analyses of 5hmC in DNA from prefrontal cortex of post-mortem AD patients, and RNA-Seq to correlate changes in 5hmC with transcriptional changes. We identified 325 genes containing differentially hydroxymethylated loci (DhMLs) in both discovery and replication datasets. These are enriched for pathways involved in neuron projection development and neurogenesis. Of these, 140 showed changes in gene expression. Proteins encoded by these genes form direct protein-protein interactions with AD-associated genes, expanding the network of genes implicated in AD. We identified AD-associated single nucleotide polymorphisms (SNPs) located within or near DhMLs, suggesting these SNPs may identify regions of epigenetic gene regulation that play a role in AD pathogenesis. Finally, using an existing AD fly model, we showed some of these genes modulate AD-associated toxicity. Our data implicate neuronal projection development and neurogenesis pathways as potential targets in AD. By incorporating epigenomic and transcriptomic data with genome-wide association studies data, with verification in the Drosophila model, we can expand the known network of genes involved in disease pathogenesis and identify epigenetic modifiers of Alzheimer's disease.